Gold Nanoclusters in Cancer Photothermal Therapy: Mechanisms, Theranostic Applications, and Clinical Translation Over the Last Decade - Jenan Atiyah Ghafil; Bashar Ibrahim; Nihad Taha Mohammed Jaddoa (World Journal of Experimental Biosciences, 2025)
This last decade has seen the rise of gold nanoclusters (AuNCs) as a new, revolutionary class of photothermal agents for cancer therapy. The AuNCs (
Keywords: Gold nanoclusters (AuNCs), Nanotheranostics, Photothermal conversion efficiency, Photothermal therapy, Precision oncology.